THE INFLUENCE OF WORKING PERIOD ON WORK DUE TO LUNG DISEASES IN PRODUCTION WORKERS OF NATURAL STONE PROCESSING, IN TULUNGAGUNG - Dinata, Mulya; Sincihu, Yudhiakuari; Suwasanti, Niluh; Rihadi, Lukas Slamet; Steven, Steven; Darmadi, Epriyanto Tri; Wulansari, Nurlita (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Background of the Problem: In 2000, deaths caused by air pollution in the world reached 57,000 people per year and it is estimated that over the next 20 years this figure will increase to close to 14% or 0.7 per year. According to Calvin, 2020, in Gold Mining, incidents of Silica exposure among workers aged 45-55 years out of 2255 people, it was found that 1592 (71%) people died. From the number above, there were 1296 people (81%) suffering from silicosis and pulmonary Tuberculosis (TB). Chemical dust (Silica) causes lung disorders, which is one of the Occupational Lung Diseases. The above process has a danger to the environment and workers. According to BPJS Employment 2022, the number of cases of KK (working accidents) and PAK (occupational diseases) in 2021 is 234,370 cases.Method of Research: Population of 100 workers aged 20 – 61 years, Natural Stone Processors located in Tulungagung, East Java, Indonesia. Workers inspection: (1) Interview and physical examination of workers, (2) Supporting examination: Spirometry and Thorax photos, (3) Work Environment Testing consisting of: Work climate, dust, gas (NO2, CO2).Results: Worker habits: smoking as much as 55%, PPE (Personal Protective Equipment) used by the majority of cloth masks 71%, chemical dust (Silica) highest 4.6995 mg/m3, Climate in the workplace (temperature >32°C). These conditions can influence the occurrence of occupational lung disorders. Lung examination of Natural Stone processing workers in Tulungagung showed lung function disorders in 61 people (61%) and thorax photo examination showed abnormalities in 11 people (11%). WorkingPeriod has an influence on Occupational Lung Disease with a significance value of 0.03 (p-value < 0.05), with a confidence level of 95%.Conclussion: Working Period influences Occupational Lung Disease in workers in the production department of the Natural Stone Processing Company, in Tulungagung (1). Other factors that are suspected to influence the health of workers include: Occupational Lung Disease, namely smoking habits, not using the correct PPE, a dusty work environment (chemical substances) and a workplace climate with temperatures above the recommended values (2).Keywords: PAK, KK, APD, Silica, Working Period, Lung Disease due to work